2023
DOI: 10.3390/w15112070
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Oxic–Anoxic Process under Low Dissolved Oxygen for Nitrogen Removal from Low COD/N Tropical Wastewater

Abstract: Conventionally, nitrification in biological nitrogen removal (BNR) requires high dissolved oxygen (DO) concentrations (>2 mg L−1), making the process energy intensive. Recent studies have shown that efficient ammonium removal and energy reduction can be realized by operating the nitrification at low DO concentrations (<1 mg L−1). In this study, the low-DO oxic anoxic (low-DO OA) process was operated in a pilot-scale sequencing batch reactor (SBR) over 218 days to evaluate the feasibility of nitrogen remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The influent is described for three conditions of influent variation: low C/N ratio (below 1), intermediate C/N ratio (equal to 1), and high C/N ratio (above 1). The ratio value was defined considering previous studies conditions for WWTPs [1,5,25,26]. The low-strength stream data from [28] and high-strength stream data adapted from [4] were used in this study.…”
Section: Implementation Of the Control Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The influent is described for three conditions of influent variation: low C/N ratio (below 1), intermediate C/N ratio (equal to 1), and high C/N ratio (above 1). The ratio value was defined considering previous studies conditions for WWTPs [1,5,25,26]. The low-strength stream data from [28] and high-strength stream data adapted from [4] were used in this study.…”
Section: Implementation Of the Control Strategiesmentioning
confidence: 99%
“…Water 2023, 15, 4015 2 of 20 Novel technologies have been studied over the years to overcome the effects of nitrogen overloads, such as the configurations of oxic-anoxic treatment process [5], the combined nitrification/denitrification and deammonification process, complete autotrophic nitrogen removal over nitrite (CANON) [6], single reactor system for high-activity ammonia removal over nitrite (SHARON), and the anaerobic ammonium oxidation (Anammox) [7][8][9][10]. The combined SHARON-Anammox process has been reported to present a substantial advantage in nitrogen removal, reducing operational costs and benefiting resource recovery [4,7,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anammox technology, which has garnered significant attention in recent years, employs anammox bacteria to transform ammonium nitrogen and nitrite nitrogen into nitrogen under anaerobic conditions [18]. However, these nitrogen-removal bacteria are all sensitive to environmental factors such as dissolved oxygen (DO) [19][20][21], the C/N ratio [22,23], temperature [24][25][26], pH [27,28], and so on. Numerous studies have confirmed the negative impact of nano-ZnO on the biological nitrogen removal (BNR) process in wastewater due to its antibacterial properties [29][30][31].…”
Section: Introductionmentioning
confidence: 99%